Expression of CD9 on porcine lymphocytes and its relation to T cell differentiation and cytokine production. (August 2021) - Milburn, Jemma V.; Hoog, Anna M.; Winkler, Simona; van Dongen, Katinka A.; Leitner, Judith; Patzl, Martina; Saalmüller, Armin; de Luca, Karelle; Steinberger, Peter; Mair, Kerstin H.; Gerner, Wilhelm
Abstract: In this work, we report on two novel monoclonal antibodies, specific for porcine CD9. CD9 is a tetraspanin that is expressed on a wide variety of cells. We phenotyped porcine immune cell subsets and found that CD9 was expressed on all monocytes as well as a subset of B cells. CD9 was variably expressed on T cells, with CD4 T cells containing the highest frequency of CD9 + cells. CD9 expression positively correlated with the frequency of central memory CD4 T cells in ex vivo PBMC. Therefore, we proceeded to explore CD9 as a marker of T cell function. Here we observed that CD9 was expressed on the vast majority of long-lived influenza A virus-specific effector cells that retained the capacity for cytokine production in response to in vitro recall antigen. Therefore, the new antibodies enable the detection of a cell surface molecule with functional relevance to T cells. Considering the importance of CD9 in membrane remodelling across many cell types, they will also benefit the wider field of swine biomedical research. Highlights: Two new monoclonal antibody clones (VIV–3B3 and VIV-2E12) are specific for porcine CD9. Porcine CD9 is expressed on all monocytes and is variably expressed on lymphocytes. The frequency of CD9 + CD4 T cells correlates with central memory CD4 T cells. Long-lived T cells which respond to influenza A virus recall antigen express CD9.